2022
DOI: 10.1371/journal.pone.0263495
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to oil pollution and maternal outcomes: The Niger Delta prospective cohort study

Abstract: Background Maternal exposure to oil pollution is an important public health concern. However, there is a dearth of literature on the effects of maternal exposure to oil pollution on maternal outcomes in the Niger Delta region of Nigeria. This study was therefore designed to determine the effect of maternal exposure to oil pollution on maternal outcomes in the Niger Delta region of Nigeria. Methods Prospective cohort study design involving 1720 pregnant women followed from pregnancy to delivery was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Additionally, in a prospective cohort study examining the effects of maternal exposure to oil pollution in the Nigerian Niger Delta region, pregnant women were tracked from conception to delivery: Women in high exposure areas experienced a higher incidence of preterm birth following premature rupture of the membrane (PROM) than women in areas with low exposure to oil pollution. Even after adjusting for confounding variables, women in high exposure areas still showed a higher risk of early rupture of the membranes and preterm delivery as compared to women in low exposure areas to oil pollution [30]. This suggests once more that exposure to oil pollution is a factor in the unfavorable outcomes of pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, in a prospective cohort study examining the effects of maternal exposure to oil pollution in the Nigerian Niger Delta region, pregnant women were tracked from conception to delivery: Women in high exposure areas experienced a higher incidence of preterm birth following premature rupture of the membrane (PROM) than women in areas with low exposure to oil pollution. Even after adjusting for confounding variables, women in high exposure areas still showed a higher risk of early rupture of the membranes and preterm delivery as compared to women in low exposure areas to oil pollution [30]. This suggests once more that exposure to oil pollution is a factor in the unfavorable outcomes of pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…Different health impacts of oil spillage on oil-producing communities were reported by Ezejimofor et al, (2016), Nriagu et al, (2016), Ilevbare and Idemudia (2019) and Oghenetega et al, (2022). They observed that residency in oil spill-impacted areas affected pregnant women, induced hypertension among the residents, and negatively impacted their mental health.…”
Section: Policy Measures Available For Mitigating the Incidence Oil S...mentioning
confidence: 99%
“…16 Pregnant women resident in such crude oil polluted areas become more vulnerable to health anomalies. 17 Therefore, their utilization of primary maternal healthcare such as ANC and birth services becomes vital for the early detection and treatment of complications. 18 The objective of this study was to examine the primary maternal healthcare service utilization among pregnant women in the oil-producing Nchia-Eleme community in Nigeria.…”
Section: Introductionmentioning
confidence: 99%